High-Efficiency Secretion and Directed Evolution of Chitinase BcChiA1 in Bacillus subtilis for the Conversion of Chitinaceous Wastes Into Chitooligosaccharides - Wang, Sijia; Fu, Gang; Li, Jinlong; Wei, Xunfan; Fang, Huan; Huang, Dawei; Lin, Jianping; Zhang, Dawei (Frontiers in Bioengineering and Biotechnology, 2020)
Limitations of enzyme production and activity pose a challenge for efficient degradation of chitinaceous wastes. To solve this problem, we engineered a system for high-yielding extracellular secretion of chitinase A1 from Bacillus circulans (BcChiA1) in B. subtilis. Furthermore, an innovative chitinase high-throughput screening method based on colloidal chitin stained with Remazol Brilliant Blue R (CC-RBB) was established and used to identify three mutants with improved chitinase activity: Y10A/R301A/E327A (Mu1), Y10A/D81A/E327A (Mu2), and F38A/K88A/R301A (Mu3). Their highest specific activity reached 1004.83 ± 0.87 U/mg, representing a 16.89-fold increase in activity compared to native BcChiA1. Additionally, we found that there is a synergistic effect between BcChiA1 and a lytic polysaccharide monooxygenase from Bacillus atrophaeus (BatLPMO10), which increased the chitin processing efficiency by 50 % after combining the two enzymes. The yield of chitooligosaccharide (COS) production using the mutant Mu1 and BatLPMO10 reached 2885.25 ± 2.22 mg/L. Taken together, the results indicated that the CC-RBB high-throughput screening method is a useful tool for chitinase screening, and evolution of BcChiA1 in collaboration with BatLPMO10 has tremendous application potential in the biological treatment of chitinaceous wastes for COS production.